Efficacy of Aqueous Crude Fruit Extract of Desert Date (Balanites aegyptiaca) in Anaesthetization of African Catfish (Clarias gariepinus) Fingerlings - Wakawa, Idi Audu; Chiroma, Abubakar (Journal of Drug Delivery and Therapeutics, 2020)
Chemicals have been used to anaesthetize fish but due to their hazardous effects on the environment, fish and humans environmentally friendly plant anaesthetics are being sought. Fruit of Desert date (Balanites aegyptiaca) is nontoxic to humans but has been reported to have anaesthetic potentials on fish. This study investigates anaesthetic effect of aqueous crude fruit extract of B. aegyptiaca on African catfish (Clarias gariepinus) fingerlings. Phytochemical and proximate compositions of the fruit were screened. Exactly 120 C. gariepinus fingerlings (mean weight 32.13±2.43g and mean total length 23.88±2.11cm) were used for the experiment. A total of 10 fingerlings were exposed to each of 2.00, 2.50, 3.00, 3.50 and 4.00g/L concentrations of aqueous crude fruit extract of B. aegyptiaca and a control in 6 plastic tanks (45x28x25cm) filled with 10L of tap water. Setup was arranged in randomized block design and replicated. Temperature, dissolved oxygen, pH, free carbon dioxide and total alkalinity were monitored. Results revealed long mean induction (25.05±3.35 min) and recovery (108.35±2.45 min) times with resultant mortalities (40%) of C. gariepinus fingerlings. significant correlation (P<0.01) exists between concentration of the fruit extract and induction time as well as between fruit extract concentrations and survival of fingerlings. Aqueous crude fruit extract of B. aegyptiaca is, therefore, not effective for anaesthetization of C. gariepinus fingerlings hence should be avoided. Keywords: Anaesthetic, Balanites aegyptiaca, Clarias gariepinus